Shear Capacity of Reinforced Concrete Beam with an Opening Retrofit Using Steel Fiber and Metakaolin - Zulkifli, Batrisyia; Ali, Noorwirdawati; Abdul Hamid, Noor Azlina; Salleh, Norhafizah; Abdullah, Siti Radziah (Journal of Structural Monitoring and Built Environment, 2023)
This study presents the experimental work of reinforced concrete beam with opening at shear zone and added with steel fibre and metakaolin to increase the shear capacity of the beam. A total of five (5) beams were casted and tested under four-point bending test. One beam served as the control specimen, two beams were beams with one and two opening respectively while the other two beams were beams with added steel fibre and metakaolin. The type of steel fibre used was a hooked-end steel fibers with the dimensions of 0.9mm in diameter, 60mm in length, and 0.5% of steel fiber was added by volume of beam, and 5% of metakaolin by volume of beam were used. From the experimental results, it was found that the two beams with added steel fibre and metakaolin shows an increase in shear capacity compared with the beams with opening without the steel fibre and metakaolin. The highest shear force recorded was 79.11 kN (beams with added steel fibre and metakaolin) which shows an increase for about 54.3 % compared with the same beam with opening without added steel fibre and metakaolin.